Tinjauan Ekonomi Islam terhadap Praktik Painrang Berasa (Peminjaman Beras) di Desa Bontolempangang Kabupaten Gowa - Saleha, St.; Anwar, Nurfiah; Darussalam, Andi Zulfikar (AHKAM, 2024)
This research aims to describe the practice of "painrang berasa" (borrowing rice) paid in cash in the village of Bontolempangang, Gowa Regency, and analyze the Islamic economic perspective on this practice. The research approach used is descriptive qualitative with field research methods. Data was collected through recording, analysis, and interpretation of the lending and borrowing practices in the Bontolempangang village. The research findings indicate that the practice of painrang berasa occurs when the muqridh (lender) lends rice to the muqtaridh with an agreement that repayment will be made in cash at the current price of rice at the time of borrowing. The agreement is established through ijab qabul, whether orally or in writing. In terms of validity requirements, this agreement complies with Islamic legal provisions as both the muqridh and muqtaridh are legally competent or mature, and the debt object is valid, whether in the form of rice or money. However, the existence of two forms of transactions, namely short-term and long-term painrang berasa, indicates that one of these transaction forms may not align with the principles of Islamic economic law. Therefore, this research contributes to understanding lending and borrowing practices from an Islamic economic perspective in the village of Bontolempangang, Gowa Regency. The conclusion of this research emphasizes the need for a reassessment of the painrang berasa practice in the context of Islamic economics to ensure compliance with established principles.